Dynamics of the Romanian Illegal Drug Markets - Irina Caunic; Mircea Tulica (CES Working Papers, 2011)
Globalization has led to an increase in commercial activities running on the illegal markets, its dynamics being largely determined by the balance between profitability and the major risks involved. Revenues are significant, one example being those obtained from drug industry. In recent years, illicit drug trafficking has seen in Romania an unprecedented escalation, as a result of market liberalization and the movement of persons and because of the extending the phenomenon both among producers and consumers. This article examines the size of the Romanian illegal drug markets, the countries of origin and drug transit routes, as well as the profits made by the drug trafficking networks.
Keywords: 330; drug trafficking; profit; illegal markets; cocaine; heroin; psychoactive substances Romania